Efforts to Develop Rapid Technology of In Vitro Transcription and Translation in Vaccine Synthesis in Indonesia - Muhamad Ali (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2015)
Production of functional protein (including vaccine) using conventional technology in embryonated chicken eggs is laborious and lengthy. The use of chemical synthesis is not practical for peptides longer than 20 residues. In contrast, in vitro transcription and translation technology can directly utilize polymerase chain reaction (PCR) product as template for vaccine synthesis within two hours accurately. Moreover, up to 1-10 mg/ml protein can be produced using the technology compared to conventional method that only gives approximately one dose per egg. In this review, advantages and disadvantages of animal vaccine generation using conventional and in vitro methods would be described. In vitro transcription and translation technology can be considered as the most practical and efficient technique for rapid screening and generating new animal vaccines.